2018
DOI: 10.1371/journal.pone.0206120
|View full text |Cite
|
Sign up to set email alerts
|

Drug therapy problems and contributing factors in the management of heart failure patients in Jimma University Specialized Hospital, Southwest Ethiopia

Abstract: BackgroundDrug therapy problem (DTP) is any unwanted incident related to medication therapy that actually or potentially affects the desired goals of treatment. Heart failure (HF) patients are more likely to experience DTP owing to multiple prescriptions and comorbidities. Despite the serious negative impact of DTP on treatment outcomes, there is a dearth of study on DTP among HF patients in Ethiopia.ObjectiveThe main aim of this study was to assess the prevalence and contributing factors of DTP among ambulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
115
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(143 citation statements)
references
References 36 publications
(44 reference statements)
22
115
5
1
Order By: Relevance
“…This study is one of the first research to have determined the factors associated with the occurrence of DTPs at the primary care level (24), by employing the theoretical framework proposed by Cipolle et al Moreover, it appears to be the first study to have established DTP-associated factors among general ambulatory patients, by using the aforementioned methodology. In line with published evidence (24,28,29), polymedicated patients were more likely to have a higher number of DTPs. The second characteristic most strongly associated with the occurrence of three or more DTPs was type 2 diabetes.…”
Section: Quantitative Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…This study is one of the first research to have determined the factors associated with the occurrence of DTPs at the primary care level (24), by employing the theoretical framework proposed by Cipolle et al Moreover, it appears to be the first study to have established DTP-associated factors among general ambulatory patients, by using the aforementioned methodology. In line with published evidence (24,28,29), polymedicated patients were more likely to have a higher number of DTPs. The second characteristic most strongly associated with the occurrence of three or more DTPs was type 2 diabetes.…”
Section: Quantitative Resultssupporting
confidence: 85%
“…In addition, various studies have demonstrated its effectiveness on clinical (14,15,(17)(18)(19)(20)(21)(22)(23)(24), economic (17,22,23,25) and humanistic outcomes (26,27). Other studies determined some factors associated with the occurrence of DTPs, such as polypharmacy, multimorbidity and age, yet employed methodology or clinical settings dissimilar to the present study (28)(29)(30)(31). However, to the best of authors' knowledge, until now, no study determined the associated factors of patients with chronic diseases at the primary care level as they receive CMM services that follow the theoretical framework proposed by Cipolle et al (9).…”
mentioning
confidence: 93%
“…DTPs are usually classified as: unnecessary drug therapy, the need for additional drug therapy, ineffective drug therapy, too low dosage, too high dosage, adverse drug reaction (ADR), and non-compliance. 9,10 Antimicrobial drug therapy problems refers to incorrect and inappropriate utilization of antimicrobials which affect patient health outcomes and even result in bacterial resistance. 11 Literature reviews regarding DTPs indicated that a total of 199 DTPs were identified among patients receiving outpatient antimicrobial therapy in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 DTP is any unwanted incident related to medication therapy that actually or potentially affects the desired goals of treatment. 4 DTP is an important public health problem and has been heightened in recent years. 5 Relatively 28% of all emergency department visits and 5 to 10% of all hospital admissions are drug related.…”
Section: Baclgroundmentioning
confidence: 99%